A study on compressive strength, static and dynamic elastic modulus of self-compacted concrete contained nanomaterials - Rahmat Madandoust (Journal of Structural and Construction Engineering, 2021)
In this study, the influence of different kinds of nanomaterials such as Nano oxides of Silica (NS), Aluminum (NA) and Copper (NC) on compressive strength (f’c), static elastic modulus (Ee), relationship between f’c and Ee and the relationship between static and dynamic elastic modulus (Ed) of self-compacted concrete are examined. The nanomaterials are used as the binder in replacement of Portland cement. For this purpose, standard cylindrical samples containing NS, NA and NC with amounts of 1.5, 0.25 and 0.25%, respectively, were tested between 3 and 90 days. The f’c, Ee and Ed are evaluated according to ASTM C39/39M-16b, ASTM C469/C469M-14 and ASTM C597-16, respectively. Results indicate that adding Nanomaterials lead to improvement of f’c and elasticity module. New relations between f’c and Ee and, also, linear relation between Ee and Ed defined for this kind of self-compacted concretes, and it was observed that type and quantity of the Nanomaterials have impact on these relations. The experimental data of Ee at early ages are smaller than the calculated values of Ee from recommended equations by ACI 318-14, ACI 363-10, and CSA A23.3-14. The difference between experimental data and calculated values of Ee is decreased when f’c increases. when the f’c is higher than 45 MPa, the experimental data of Ee are higher than the calculated values of ACI 363-10. The study indicate that the Ed is always greater than the Ee and the difference between Ed and Ee is decreased when f’c increases. It was found that the differences between Ed and Ee in this study are greater than the differences between Ed and Ee in BS 8110: 2 and the other studies.